Economic and environmental packaging sustainability: A case study - Iván González-Boubeta; Mar Fernández-Vázquez-Noguerol; Pablo Domínguez-Caama\~no; José Carlos Prado-Prado (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: The aim of this paper is to analyze the suitability of the packaging strategy of an important Spanish agro-food company, regarding to economic and environmental sustainability. Design/methodology/approach: Three different types of packaging are analyzed to obtain a diagnostic of the initial situation. In this process, cost and carbon footprint are calculated in order to measure the economic and environmental impacts, respectively. Then, a new packaging allocation logic is proposed with the aim of improving both aspects. Findings: The results show that the carbon footprint is strongly and positively affected by the cost reduction, showing the viability of a win-win relationship between both aspects. Research limitations/implications: The strength of this win-win relationship may be conditioned by the input values considered in this case study. Conversion factors used to calculate carbon footprint vary a lot among researchers, showing the need of standardization in this topic. Practical implications: Since the existence of a positive relationship between economic and environmental sustainability has been demonstrated, organizations should find this kind of situations in themselves to satisfy their own stakeholders. Originality/value: This article shows the potential of unite waste elimination with eco-friendly activities with the aim of increasing the competitiveness of companies. This paper also contributes to the knowledge of economic and environmental sustainability and reinforces theoretical aspects, paving the way for further research on these topics.
Keywords: 650; sustainability; reusable packaging; disposable packaging; distribution; transport